Synthesis and characterisation of silica and magnetic oxide nanocomposite modified poly (4,4’-cyclohexylidene bisphenol oxalate) for DNA extraction - A., Albalawi Aisyah Nawaf (2019)
In the present project, a novel polymer has been synthesised as polyester- poly(4,4'- cyclohexylidene bisphenol oxalate) (PBPZO) by the condensation of oxalyl chloride with 4,4’-cyclohexylidene bisphenol, where its efficacy was tested for the solid phase extraction of DNA. Surface modification of polymer is also applied by using reinforcement (inorganic oxide) such as iron oxide nanoparticles and silica nanoparticles. Iron oxide (Fe3O4) with the particle size 50-100 nm, microcrystalline cellulose (MCC) with 20 μm particle size, urea, HNO3, and NaOH have been used for the surface modification of PBPZO by physically mixing dispersed solutions. A novel PBPZO/ silica nanocomposite was prepared by two methods. The first method was by mixing PBPZO solution with fumed silica NPs that follow mixing solution method. The second method was by mixing 4, 4'-cyclohexylidenebisphenol monomer solution in the presence of three different ratios of fumed silica (11 nm) NPs: 3.7 wt.%, 7.0 wt.% and 13.0 wt.%. The product of synthesised polymer is a white powder with an average particle size of 162.45 nm, and PBPZO/ cellulose/ magnetite composite, which was black powder with magnetic properties characterised by vibrating sample magnetometer (VSM), scanning electron microscopy (SEM) and Brunauer- Emmett- Teller (BET) analysis. Furthermore, polymer nanocomposites of PBPZO/ silica were characterised by SEM analysis and BET. The average diameter of PBPZO/ silica (3.7 wt.%), PBPZO/ silica (7 wt.%), PBPZO/ silica (13 wt.%) and PBPZO/ silica solution were 67.8 nm, 61.5 nm, 60.6 nm and 55.9 nm respectively. The structure of polymer and polymer nanocomposites were investigated by Fourier-transform infrared spectroscopy (FTIR) and energy dispersive (x-ray) analysis (EDX). The thermal properties of the PBPZO, PBPZO-MCC-magnetite composite and PBPZO/ silica nanocomposites were studied by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The solid phase application of the resulting polymer and polymer nanocomposites have been applied in DNA extraction, with the results indicating that the extraction efficiency is strongly influenced by the weight of polymer and polymer nanocomposites and binding buffer type. Among three types of buffers tested, 2 M GuHCl/ EtOH, NaCl and phosphate buffered saline (PBS) buffers, GuHCl buffer produced the most satisfactory results in terms of extraction efficiency for PBPZO and PBPZO nanocomposites that equal 2448 (ng/uL), 7237.5 (ng/uL) and 3370 (ng/uL) with percentages of DNA extraction (16.2%, 72.4%, and 24.4% ) for PBPZO, PBPZO/ cellulose/ magnetite composite and PBPZO/ silica nanocomposites respectively. The results of the study indicated that the developed PBPZO, PBPZO/ cellulose/ magnetite composite, and PBPZO/ silica nanocomposites can be a potential candidate for the high efficiency extraction of DNA.